2020
DOI: 10.1248/bpb.b19-00953
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> Inhibitory Effects of Sesamin on CYP4F2 Activity

Abstract: Sesamin is a major lignan in sesame seeds, and a recent meta-analysis of controlled trials indicated that sesamin intake decreases blood pressure. The antihypertensive effect of sesamin has been suggested to be due to sesamin-mediated suppression of 20-hydroxyeicosatetraenoic acid production catalyzed by CYP4F2. However, the detailed mechanism underlying inhibition of CYP4F2 function by sesamin remains unclear. In this study, the effects of sesamin on catalytic activity of CYP4F2 were investigated in vitro. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…While the specific activity of CYP4F2 for linezolid 2-hydroxylation was 6-fold lower than CYP2J2, the expression level in liver for CYP4F2 is greater, ranging up to 30 pmol/mg protein (Michaels and Wang, 2014). Sesamin, a known inhibitor of CYP4F2 (Watanabe, et al, 2020) was shown to cause nearly complete inhibition of linezolid 2-hydroxylation in both recombinant CYP4F2 and human liver microsomes (Figure 5). At first glance, this could be viewed as contrasting the result obtained for LKY-047 in liver microsomes showing the aforementioned ~50-60% contribution by CYP2J2.…”
Section: Discussionmentioning
confidence: 99%
“…While the specific activity of CYP4F2 for linezolid 2-hydroxylation was 6-fold lower than CYP2J2, the expression level in liver for CYP4F2 is greater, ranging up to 30 pmol/mg protein (Michaels and Wang, 2014). Sesamin, a known inhibitor of CYP4F2 (Watanabe, et al, 2020) was shown to cause nearly complete inhibition of linezolid 2-hydroxylation in both recombinant CYP4F2 and human liver microsomes (Figure 5). At first glance, this could be viewed as contrasting the result obtained for LKY-047 in liver microsomes showing the aforementioned ~50-60% contribution by CYP2J2.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for interactions of sesamin with drugs metabolized by CYP2C9 in humans is not well characterized and warrants additional monitoring. Furthermore, there is evidence that sesamin can inhibit the activities of cytochrome P450 3A4 and cytochrome P450 4F2 12,55,159–161 . Inhibition of CYP3A4 is associated with increased plasma concentrations of γ-tocopherol.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, there is evidence that sesamin can inhibit the activities of cytochrome P450 3A4 and cytochrome P450 4F2. 12,55,[159][160][161] Inhibition of CYP3A4 is associated with increased plasma concentrations of γ-tocopherol. CYP3A4 also participates in the metabolism of a wide variety of substrates including retinoic acid, bile acid, testosterone, estrogen, cholesterol, dietary chemicals, and environmental toxins, as well as drugs such as acetaminophen, codeine, and cyclosporin A and the novel heart rate-lowering agent, ivabradine.…”
Section: Safetymentioning
confidence: 99%
“…A recent meta-analysis indicated that intake of sesamin can decrease blood pressure. The antihypertensive effect of sesamin may be related to the sesamin-mediated inhibition of CYP4F2-catalyzed 20-hydroxyl eicosaenoic acid production [ 72 ]. Sesamin can also effectively decrease serum and liver fat levels [ 73 ].…”
Section: Functions and Activities Of Sesame Protein And Sesame Lignansmentioning
confidence: 99%